Diffusion strategies for face swiping medical service using evolutionary game theory. Issue 8 (2nd August 2021) - Wang, Xiaojia; Cheng, Peiling; Zhu, Keyu; Xu, Sheng; Zhang, Shanshan; Xu, Weiqun; Guan, Yuxiang
Abstract: Face swiping is the action of registering facial recognition data with a biometric authentication application. Face swiping‐based medical services (FSMSs) is an emerging measurement technology underpinning modern intelligent medical services in China. In view of convenience in the delivery of medical services and the potential to reduce medical costs, FSMSs have become an important part of China's medical reform. However, modelling its eventual uses has not been fully explored in theory and practice, and this is hindering the take up of FSMSs in China. In this paper, we build an evolutionary game model to explore three stakeholders—policy makers, hospitals, and patients—and their dynamic interdependence of their decision‐making when adopting FSMS. Based on our game theoretic analysis, we develop a novel model to track the behaviour of these three stakeholders and analyse the corresponding payoff matrix to establish the replication dynamic equation (RDE) for the game. Further, we then use RDE to calculate the different stability points of players and determine the game's stable strategy. Finally, we validate the proposed model with a detailed simulation. Our observations may benefit not only FSMS participants but also several other forms of medical services and industries.